Applying ELSA Speak Software in the Pronunciation Class: Students’ Perception - Ita Sarmita Samad; Aminullah Aminullah (Edumaspul: Jurnal Pendidikan, 2019)
This study aims at finding out the students’ perception towards the application of ELSA Speak software in their pronunciation class. A total number of 12 students are involved in this present study. Descriptive quantitative research design is applied in this study. It utilizes questionnaire to collect data and Likert-Scale to analyze the data. The result shows that students consider that the software is very good to be applied in learning pronunciation.